Corrosion test device and test method for realizing multiple stress levels of reinforcing steel bar
By designing a steel bar corrosion test device including a loading system, a chlorine corrosion system and a test and control system, the problems of complex device structure, inconvenient load application and inability to conduct multiple stress level corrosion tests at the same time in the prior art are solved, and multiple stress level corrosion tests on steel bars are realized, which improves the test efficiency and authenticity.
Patent Information
- Application Number
- CN202510210212.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing reinforcement stress corrosion test equipment has complex structure and is inconvenient to apply loads. It is impossible to conduct corrosion tests under multiple stress levels at the same time, which limits the evaluation of the corrosion performance of the reinforcement.
A corrosion test device including a loading system, a chlorine corrosion system and a test and control system was designed to apply various stress levels to the steel bars through a loading frame and a load drive device, and data acquisition and monitoring are carried out through a chlorine corrosion system and an electrochemical workstation.
The corrosion test of various stress levels of steel bars of different diameters is realized, which simplifies the test process, improves the test efficiency, and can more realistically simulate the corrosion conditions of steel bars under the chloride salt environment and load coupling effect.
Smart Images

Figure CN119915712A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material stress testing devices, and in particular to a corrosion testing device and a testing method for realizing multiple stress levels of steel bars. Background Art
[0002] In marine environments, the durability damage of concrete structures caused by steel corrosion has become a major disease in civil engineering, seriously affecting the service life and safety and reliability of structures. In actual engineering, reinforced concrete structures in chloride salt environments such as oceans and salt lakes are not only affected by degradation reactions such as chloride ion erosion and chemical corrosion, but also by loads. Under the combined action of loads and corrosive media, stress corrosion occurs in the steel bars. Under the action of stress corrosion, the corrosion current density of steel bars will increase, the corrosion rate will accelerate, and the appearance and expansion of corrosion holes and pits in the steel bars will be aggravated. For concrete structures using stainless steel bars, corrosion cracks will also occur on the surface of the steel bars. After the steel bars are corroded, in addition to the reduction of their own mechanical properties, they will also cause a series of durability problems such as cracking and peeling of the concrete protective layer, affecting the normal use of the structure. Therefore, conducting experimental research on the stress corrosion behavior of various types of steel bars has very important theoretical significance and engineering application value for structural durability evaluation and service life prediction.
[0003] However, the structure of the test device for stress corrosion of steel bars is relatively complex and heavy, it is difficult to apply load to the steel bars, and it is inconvenient to test the corroded parts. In addition, if there is a device that can perform corrosion tests under multiple stress levels at the same time, it will be easier to evaluate the corrosion performance of steel bars.
[0004] The Chinese Patent Database has published a stress corrosion test device and test method for metal rod materials, with publication number: CN101109691A, publication date: January 23, 2008. The device includes a test tank, a metal rod to be tested, a dynamometer and a dowel rod; the test tank is closed at the bottom and open at the top, with a slot for the dowel rod to pass through and a nut to fix the dowel rod position at the end; both ends of the metal rod are connected to the dowel rod; the metal rod is covered with a PVC tube, and rubber plugs are provided at both ends of the PVC tube. The metal rod passes through the rubber plugs, and the rod can be freely extended and deformed after being stressed; a tee is provided in the middle of the PVC tube for replacing the corrosion solution; and a dynamometer for monitoring the tension of the dowel rod is placed on the test tank. By changing the pH value of the corrosion solution in the PVC tube and the duration of different tensions applied to the metal rod to be tested, the stress corrosion of the metal rod material can be observed. The shortcomings of this device are: the loading frame is made of reinforced concrete and cannot be modified once it is formed; the load is applied by screwing the nut on the force transmission rod outside the dynamometer, which is inconvenient to use, the applied load level is limited, and multiple stress corrosion tests cannot be carried out simultaneously. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects in the prior art and provide a corrosion test device and a test method for realizing multiple stress levels of steel bars, which can simultaneously carry out stress corrosion tests on steel bars of different diameters. The device has a simple structure and a small size, can accurately apply different stresses to the steel bars, facilitates data collection of corrosion parts, and improves test efficiency.
[0006] The object of the present invention is achieved as follows: a corrosion test device for realizing multiple stress levels of steel bars, comprising a loading system, a chloride corrosion system and a test control system, wherein the loading system comprises a loading frame and a load driving device arranged on one side of the loading frame, wherein the loading frame comprises a left end plate and a right end plate arranged opposite to each other, and a left transverse partition and a right transverse partition are movably arranged between the left end plate and the right end plate, and three independent steel bar test sections are formed inside the loading frame through the left transverse partition and the right transverse partition; the load driving device comprises a through-core jack arranged on one side of the right end plate, the output end of the through-core jack is connected to a force transmission rod fixed on the right end plate, the input end of the through-core jack is connected to the output shaft end of a hydraulic pump connected to an oil pressure gauge, the force transmission rod passes through the right end plate and extends to one side of the left end plate and is threadedly connected to one end of a connecting sleeve, the other end of the connecting sleeve is threadedly connected to a test steel bar, and the test steel bars of the three independent steel bar test sections are connected in series through the connecting sleeve and the force transmission rod.
[0007] When the present invention is working, the basic structure of the loading frame is built by the left end plate, the right end plate and the upper and lower screw rods, and the left transverse partition and the right transverse partition are movably arranged between the left end plate and the right end plate to form three independent steel bar test sections. The load is applied to the test steel bars of different diameters in each section through the force transmission rod to keep them in different stress states, so as to realize stress corrosion test of the test steel bars at multiple stress levels at the same time. The device of the present invention has a simple structure, a small volume, is easy to build, conforms to the actual corrosion environment, can effectively simulate the corrosion of the test steel bars under the coupling effect of chloride salt environment and load, and provides a durability evaluation basis for the steel bars working in corrosive environments such as chloride salts.
[0008] Compared with the prior art, the present invention has the following beneficial effects:
[0009] First, the loading frame adopts the form of a reaction frame, which has sufficient strength to keep the steel bars to be corroded under a high stress state for chloride corrosion test, more realistically simulating the stress corrosion state of the steel bars in the concrete pore solution. The results of the experimental research are closer to the corrosion conditions of the steel bars in service, providing a durability evaluation basis for the steel bars working in corrosive media such as chloride salts.
[0010] Second, the device can simultaneously carry out stress corrosion tests on multiple steel bars to be tested under various stress levels, simplifying the test process and facilitating comparative analysis of steel bar stress corrosion test results. In addition, the device is small in size, simple in structure, and easy to operate.
[0011] Third, a through-hole jack was selected as the driving loading device, and based on the actual strain measured by the strain gauge, Hooke's law was used to calculate the real-time stress to monitor the stress loss of the test steel bars. When the strain decreased and the stress decreased, the torque wrench was used to adjust the anchor nuts at both ends of the loading frame in time to correct the stress to the target level, thereby ensuring that the load value of the test steel bars remained basically unchanged during the entire corrosion process, solving the problem of increased test errors due to stress reduction caused by device relaxation.
[0012] Fourthly, the test device of the present invention can complete the installation of the entire loading frame and data measurement using common components and instruments. At the end of the test, the device can be disassembled, cleaned and stored to reduce the impact on the next test.
[0013] Furthermore, the left end plate, the right end plate, the left transverse partition and the right transverse partition are connected and fixed by two groups of upper and lower threaded rods which are symmetrically arranged up and down. A pair of steel pads are respectively arranged at the connection between the left end plate, the right end plate, the left transverse partition and the right transverse partition and the upper and lower threaded rods, and are tightened and fixed by anchor nuts. The left end plate, the right end plate, the left transverse partition and the right transverse partition are all made of solid steel plates with a thickness of 20 to 40 mm.
[0014] Furthermore, the chloride salt corrosion system includes a corrosion tank, the tank body of which is provided with through holes relatively to each other, the test steel bars are placed in the corrosion tank and pass through the through holes on both sides, the corrosion solution is poured into the corrosion tank, a stainless steel plate is provided on the lower side of the corrosion tank, the stainless steel plate and the test steel bars are respectively electrically connected to the negative pole and the positive pole of an external DC regulated power supply through wires; an upper cover is connected to the top of the corrosion tank, a reference electrode and an auxiliary electrode are inserted into the corrosion tank through the reserved through slots of the upper cover, and the reference electrode, the auxiliary electrode and the test steel bars are respectively electrically connected to the electrochemical workstation of the external test and control system through wires.
[0015] Furthermore, the test control system also includes a strain gauge adhered to the surface of the test steel bar, and the strain gauge is electrically connected to the strain meter through a wire.
[0016] Furthermore, a rubber plug with a central penetration is provided at the junction of the through hole and the test steel bar, and the surface of the rubber plug is coated with an epoxy resin sealing layer.
[0017] Furthermore, the corrosion tank is made of acrylic material, and a drain valve is provided at the bottom of the corrosion tank.
[0018] Furthermore, the upper and lower threaded rods and the force transmission rods are all made of prestressed threaded steel bars, with diameters of 30 to 60 mm and standard tensile strength values of 785 to 1080 MPa.
[0019] A corrosion test method for realizing multiple stress levels of steel bars, using electric current to accelerate corrosion, comprises the following steps:
[0020] Step 1: Adjust the positions of the left and right transverse partitions so that the test sections divided by them meet the test space required by each section of the test steel bars;
[0021] Step 2: The test steel bar passes through the through hole reserved on the corrosion groove, and a rubber plug is sleeved on the surface of the test steel bar at the junction, and fits the outer pores of the corrosion groove;
[0022] Step 3: Build the loading frame, and connect the dowel rod, connecting sleeve and test steel bar from left to right. The two ends of the connecting sleeve are respectively connected with the dowel rod and the test steel bar by threads. A pair of steel pads are respectively set at the connection between the left end plate, the left diaphragm, the right diaphragm, the right end plate and the dowel rod, and tightened and fixed by anchor nuts. Repeat this operation until the connection of the three independent steel bar test sections is completed, and the dowel rods of each section are fixed on the loading frame;
[0023] Step 4: Grind the surface of the test steel bar exposed outside the corrosion tank until the surface is smooth and flat, paste the strain gauge on the polished part, and electrically connect the strain gauge to the strain meter through a wire;
[0024] Step 5: Install a through-hole jack on one side of the right end plate of the loading frame and connect it to the force transfer rod. Slowly increase the load through a manual hydraulic pump, check the deviation of the load position, ensure that all components of the loading frame are operating normally, and then continue to apply the load steadily. When the oil pressure gauge reading reaches the set load, tighten the anchor nut to fix the force transfer rod on the right end plate. The load is transferred to each section of the test steel bar through the force transfer rod to maintain different stress states. Remove the through-hole jack to complete the load application, and then use epoxy resin to apply the rubber plug to seal the corrosion groove; according to the stress formula σ=F / A, the corrosion test of steel bars under different stress levels can be achieved, where σ is stress in MPa, F is the applied load in N, and A is the cross-sectional area of the test steel bar in mm 2 ; When the diameters of the test steel bars of each section are different and the cross-sectional areas A are different, corrosion tests of steel bars under various stress levels can be carried out simultaneously;
[0025] Step 6: Prepare saturated Ca(OH) 2 The solution is poured into the corrosion tank as a corrosion solution, and the liquid level is kept above the top surface of the test steel bar to saturate the Ca(OH) 2The solution simulates the concrete pore solution and soaks the test steel bars for 8 to 10 days to form a stable passivation film on the surface of the test steel bars. After the steel bars are passivated, analytically pure sodium chloride is added to the simulated concrete pore solution step by step to gradually increase the concentration range until the steel bars are depassivated. During this period, the concentration range increases by one level every 24 hours. After each level of concentration increase, the open circuit potential of the test steel bars is tested using an electrochemical workstation, and whether the steel bars are depassivated is determined according to national standards. When the steel bars are depassivated, the accumulated chloride ion concentration in the simulated concrete pore solution is the critical chloride ion concentration.
[0026] Step 7: The judgment condition of steel bar depassivation is: when the open circuit potential is greater than -250mV, it means that the steel bar is not depassivated; when the open circuit potential is between -250 and -400mV, it means that the steel bar may be depassivated; when the open circuit potential is less than -400mV, it means that the steel bar has been depassivated;
[0027] Step 8: After the steel bar is depassivated, it enters the stress corrosion stage; a stainless steel plate connected to a wire is placed at the bottom of the container and connected to the negative electrode of the DC stabilized power supply. A wire is connected to the surface of the test steel bar and connected to the positive electrode of the DC stabilized power supply. The corrosion solution is used as the conductive medium to form a closed loop; the DC stabilized power supply is connected to the target current or voltage to start the accelerated corrosion process of the steel bar under continuous load;
[0028] Step 9: Conduct electrochemical tests regularly. Before the test, turn off the DC regulated power supply to ensure that the corrosion solution is stable. The reference electrode is a saturated calomel electrode, the working electrode is the test steel bar, and the auxiliary electrode is a platinum electrode. They are electrically connected to the A, B, and C ports of the electrochemical workstation through wires to form a three-electrode test system. Set the relevant parameters of the electrochemical test, turn on the electrochemical workstation, and measure the polarization curve of the corroded steel bar. The linear polarization test overpotential ΔE is 70mV, and polarization starts from "open circuit potential -70mV" and ends at "open circuit potential +70mV". The polarization rate is 0.166mV / s, and the E-lgI curve is obtained. The instantaneous polarization current value I at the end of polarization is recorded, and the polarization curve is analyzed using the software lviumsoft that comes with the electrochemical workstation to obtain the corrosion current density i corr , or determined by the empirical formula: i corr =0.67i, i=I / A, where A is the polarization area of the steel bar, and I is the instantaneous current value when the steel bar ends polarization; after the test, for the accelerated corrosion condition of power-on, connect the DC regulated power supply to the target current or voltage, and continue the accelerated corrosion test;
[0029] Step 10: Compare the corrosion current density obtained in step 9 with the international standard value to determine the corrosion degree of the steel bar. The international standard value of the corrosion current density is: corr The value is less than 0.1μA / cm 2When the steel bar is not corroded, corr The value is 0.1~1μA / cm 2 When i corr Value is 1~10μA / cm 2 When i corr Value is 10~100μA / cm 2 When , it means that the steel bar corrosion rate is very high and a high degree of corrosion has occurred;
[0030] Step 11: During the stress corrosion period, regularly observe the formation and expansion of corrosion holes and pits on the surface of the test steel bars, as well as the initiation and expansion of stress corrosion cracks, and take photos for archiving;
[0031] Step 12: During the steel bar corrosion process, the real-time stress is calculated using Hooke's law based on the real-time strain measured by the strain gauge to monitor the stress loss of the steel bars in the corrosion test; when the strain decreases and the stress decreases, the anchor nuts at both ends of the loading frame are adjusted using a torque wrench to correct the stress to the target level;
[0032] Step 13: The corrosion period t can be preliminarily calculated according to Faraday's law.
[0033]
[0034] Where, t is the power-on time; Z Fe is the valence of iron, which is 2; F is the Faraday constant, which is 96500C / mol; M loss is the preset steel bar mass loss, in g; M Fe is the molar mass of iron, take 56 g / mol; I corr is the corrosion current, in mA;
[0035] Step 14: After reaching the preset corrosion level, the stress corrosion test is terminated; the corroded steel bars in the corrosion area are intercepted, and the relationship between the morphology, length and corrosion depth of the corrosion pits on the surface of the corroded steel bars and the stress level is observed to reveal the stress corrosion cracking mechanism; the steel bar corrosion rate is calculated using the weight loss method, and the calculation formula for the steel bar corrosion rate under stress corrosion is obtained by statistical regression test data. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram of the structure of the test device of the present invention when viewed from above.
[0037] Figure 2 for Figure 1 Section view in the AA direction.
[0038] Figure 3It is a structural schematic diagram of the left-side view of the test device of the present invention.
[0039] Figure 4 It is a schematic diagram of the structure of the corrosion tank and cover of the test device of the present invention.
[0040] Figure 5 for Figure 1 Schematic diagram of the enlarged structure at point B.
[0041] Figure 6 for Figure 1 Schematic diagram of the enlarged structure at point C in the middle.
[0042] Figure 7 for Figure 1 Schematic diagram of the structure enlarged at point D in the middle.
[0043] Among them, 1 left end plate, 2 left transverse diaphragm, 3 right transverse diaphragm, 4 right end plate, 5 upper threaded rod, 6 lower threaded rod, 7 steel pad, 8 anchor nut, 9 force transmission rod, 10 connecting sleeve, 11 test steel bar, 12 DC regulated power supply, 13 corrosion tank, 14 corrosion solution, 15 stainless steel plate, 16 wire, 17 rubber plug, 18 upper cover, 19 drain valve, 20 electrochemical workstation, 21 reference electrode, 22 auxiliary electrode, 23 strain gauge, 24 strain gauge, 25 through-hole jack, 26 oil pressure gauge, 27 manual hydraulic pump, 28 bolt hole, 29 through hole. DETAILED DESCRIPTION
[0044] Embodiment 1:
[0045] like Figures 1 to 7 A corrosion test device for realizing multiple stress levels of steel bars shown in the figure comprises a loading system, a chloride corrosion system and a test control system. The loading system comprises a loading frame and a load driving device arranged on one side of the loading frame. The loading frame comprises a left end plate 1 and a right end plate 4 arranged opposite to each other. A left transverse diaphragm 2 and a right transverse diaphragm 3 are movably arranged between the left end plate 1 and the right end plate 4. Three independent steel bar test sections are formed inside the loading frame through the left transverse diaphragm 2 and the right transverse diaphragm 3. The load driving device comprises a left end plate 1 and a right end plate 4 arranged on the right side of the loading frame. A through-hole jack 25 is provided on one side of the plate 4, and the output end of the through-hole jack 25 is connected to the force transfer rod 9 fixed on the right end plate 4, and the input end of the through-hole jack 25 is connected to the output shaft end of a hydraulic pump 27 connected to an oil pressure gauge 26. The force transfer rod 9 passes through the right end plate 4 and extends to the left end plate 1 and is threadedly connected to one end of a connecting sleeve 10. The other end of the connecting sleeve 10 is threadedly connected to a test steel bar 11. The test steel bars 11 of three independent steel bar test sections are connected in series through the connecting sleeve 10 and the force transfer rod 9.
[0046] The left end plate 1, the right end plate 4, the left transverse partition 2 and the right transverse partition 3 are connected and fixed by two groups of upper and lower threaded rods which are symmetrically arranged up and down. A pair of steel pads 7 are respectively arranged at the connection between the left end plate 1, the right end plate 4, the left transverse partition 2 and the right transverse partition 3 and the upper and lower threaded rods, and are tightened and fixed by anchor nuts 8. The left end plate 1, the right end plate 4, the left transverse partition 2 and the right transverse partition 3 are all made of solid steel plates with a thickness of 20 to 40 mm.
[0047] The chloride corrosion system includes a corrosion tank 13, on which through holes 29 are relatively provided. A test steel bar 11 is placed in the corrosion tank 13 and passes through the through holes 29 on both sides. A corrosion solution 14 is poured into the corrosion tank 13. A stainless steel plate 15 is provided on the lower side of the corrosion tank 13. The stainless steel plate 15 and the test steel bar 11 are electrically connected to the negative electrode and the positive electrode of an external DC regulated power supply 12 through a wire 16 respectively; an upper cover 18 is connected to the top of the corrosion tank 13, and a reference electrode 21 and an auxiliary electrode 22 are inserted into the corrosion tank 13 through the reserved through slots of the upper cover 18. The reference electrode 21, the auxiliary electrode 22 and the test steel bar 11 are electrically connected to the electrochemical workstation 20 of the external test and control system through the wire 16 respectively.
[0048] The test control system further includes a strain gauge 24 adhered to the surface of the test steel bar 11 , and the strain gauge 24 is electrically connected to the strain meter 23 via a wire 16 .
[0049] A rubber plug 17 with a central penetration is provided at the junction of the through hole 29 and the test steel bar 11, and the surface of the rubber plug 17 is coated with an epoxy resin sealing layer; the rubber plug 17 can prevent the corrosion solution 14 from overflowing and has a self-sealing performance to ensure the safety of the corrosion test.
[0050] The corrosion tank 13 is made of acrylic material, and a drain valve 19 is also provided at the bottom of the corrosion tank 13; the transparent acrylic material can observe the surface morphology, number of pits, pit expansion path and other characteristics of stress corrosion steel bars in real time, which is convenient for recording.
[0051] The upper and lower threaded rods and the force transmission rod 9 are all made of prestressed threaded steel bars, with diameters of 30 to 60 mm and standard tensile strength values of 785 to 1080 MPa.
[0052] A corrosion test method for realizing multiple stress levels of steel bars, using electric current to accelerate corrosion, comprises the following steps:
[0053] Step 1: Adjust the positions of the left transverse partition 2 and the right transverse partition 3 so that the test sections divided by them meet the test space required by each section of the test steel bar 11;
[0054] Step 2: The test steel bar 11 passes through the through hole 29 reserved on the corrosion groove 13, and a rubber plug 17 is sleeved on the surface of the test steel bar 11 at the junction thereof, and fits the outer pores of the corrosion groove 13;
[0055] Step 3: Build the loading frame, and connect the dowel rod 9, the connecting sleeve 10 and the test steel bar 11 from left to right. The two ends of the connecting sleeve 10 are respectively threadedly connected with the dowel rod 9 and the test steel bar 11. A pair of steel pads 7 are respectively set at the connection between the left end plate 1, the left diaphragm 2, the right diaphragm 3, the right end plate 4 and the dowel rod 9, and are tightened and fixed by the anchor nut 8. Repeat this operation until the connection of the three independent steel bar test sections is completed, and the dowel rods 9 of each section are fixed on the loading frame;
[0056] Step 4: Grind the surface of the test steel bar 11 exposed outside the corrosion groove 13 until the surface is smooth and flat, and paste the strain gauge 24 on the grinded part, and the strain gauge 24 is electrically connected to the strain meter 23 through the wire 16;
[0057] Step 5: Install a through-hole jack 25 on one side of the right end plate 4 of the loading frame and connect it to the force transfer rod 9. Slowly increase the load through the manual hydraulic pump 27, check the deviation of the load application position, ensure that the components of the loading frame are operating normally, and then continue to apply the load steadily. When the reading of the oil pressure gauge 26 reaches the set load, tighten the anchor nut 8 to fix the force transfer rod 9 on the right end plate 4. The load is transferred to each section of the test steel bar 11 through the force transfer rod 9, maintaining different stress states, remove the through-hole jack 25, complete the load application, and then use epoxy resin to apply the rubber plug 17 to seal the corrosion groove 13; according to the stress formula σ=F / A, the corrosion test of the test steel bar 11 under different stress levels can be realized, where σ is the stress in MPa, F is the applied load in N, and A is the cross-sectional area of the test steel bar in mm 2 ; When the diameters of the test steel bars of each section are different and the cross-sectional areas A are different, corrosion tests of steel bars under various stress levels can be carried out simultaneously;
[0058] Step 6: Prepare saturated Ca(OH) 2 The solution is poured into the corrosion tank as the corrosion solution 14, and the liquid level is kept above the top surface of the test steel bar 11 to saturate the Ca(OH) 2 The solution simulates the concrete hole solution and soaks the test steel bar for 8 to 10 days, so that a stable passivation film is formed on the surface of the test steel bar 11; after the steel bar is passivated, analytical pure sodium chloride is added to the simulated concrete hole solution step by step to gradually increase its concentration range until the steel bar is depassivated; during this period, the concentration range increases by one level every 24 hours, and after each level of concentration increase, the open circuit potential of the test steel bar 11 is tested using an electrochemical workstation 20, and whether the steel bar is depassivated is determined according to national standards; when the steel bar is depassivated, the accumulated chloride ion concentration in the simulated concrete hole solution is the critical chloride ion concentration;
[0059] Step 7: The judgment condition of steel bar depassivation is: when the open circuit potential is greater than -250mV, it means that the steel bar is not depassivated; when the open circuit potential is between -250 and -400mV, it means that the steel bar may be depassivated; when the open circuit potential is less than -400mV, it means that the steel bar has been depassivated;
[0060] Step 8: After the steel bar is depassivated, it enters the stress corrosion stage; a stainless steel plate 15 connected to a wire 16 is placed at the bottom of the corrosion tank 13 and connected to the negative electrode of the DC stabilized power supply 12, and a wire 16 is connected to the surface of the test steel bar 11, connected to the positive electrode of the DC stabilized power supply 12, and the corrosion solution 14 is used as a conductive medium to form a closed loop; the DC stabilized power supply 12 is connected to the target current or voltage, and the accelerated corrosion process of the test steel bar 11 under continuous load is started;
[0061] Step 9: Conduct electrochemical tests regularly. Before the test, turn off the DC regulated power supply 12 to ensure that the corrosion solution 14 is stable inside. The reference electrode 21 uses a saturated calomel electrode, the working electrode is the test steel bar 11, and the auxiliary electrode 22 uses a platinum electrode. They are electrically connected to the A, B, and C ports of the electrochemical workstation 20 through the wire 16 to form a three-electrode test system. Set the relevant parameters of the electrochemical test, turn on the electrochemical workstation 20, and measure the polarization curve of the corroded steel bar; the linear polarization test overpotential ΔE is 70mV, polarization starts from an open circuit potential of -70mV and ends at an open circuit potential of +70mV, the polarization rate is 0.166mV / s, and the E-lgI curve is obtained. The instantaneous polarization current value I at the end of polarization is recorded, and the polarization curve is analyzed using the software lviumsoft provided by the electrochemical workstation 20 to obtain the corrosion current density i corr , or determined by the empirical formula: i corr =0.67i, i=I / A, where A is the polarization area of the steel bar, and I is the instantaneous current value when the steel bar ends polarization; after the test, for the accelerated corrosion condition of power-on, connect the DC regulated power supply 12 to the target current or voltage, and continue the accelerated corrosion test;
[0062] Step 10: Compare the corrosion current density obtained in step 9 with the international standard value to determine the corrosion degree of the steel bar. The international standard value of the corrosion current density is: corr The value is less than 0.1μA / cm 2 When the steel bar is not corroded, corr The value is 0.1~1μA / cm 2 When i corr Value is 1~10μA / cm 2 When i corr Value is 10~100μA / cm 2When , it means that the steel bar corrosion rate is very high and a high degree of corrosion has occurred;
[0063] Step 11: During the stress corrosion period, regularly observe the formation and expansion of corrosion holes and pits on the surface of the test steel bar 11, as well as the initiation and expansion of stress corrosion cracks, and take photos for archiving;
[0064] Step 12: During the steel bar corrosion process, the real-time stress is calculated using Hooke's law based on the real-time strain measured by the strain gauge 23 to monitor the stress loss of the corrosion test steel bar 11; when the strain decreases and the stress decreases, the anchor nuts 8 at both ends of the loading frame are adjusted using a torque wrench to correct the stress to the target level;
[0065] Step 13: The corrosion period t can be preliminarily calculated according to Faraday's law.
[0066]
[0067] Where, t is the power-on time; Z Fe is the valence of iron, which is 2; F is the Faraday constant, which is 96500C / mol; M loss is the preset steel bar mass loss, in g; M Fe is the molar mass of iron, take 56 g / mol; I corr is the corrosion current, in mA;
[0068] Step 14: After reaching the preset corrosion level, the stress corrosion test is terminated; the corroded steel bars in the corrosion area are intercepted, and the relationship between the morphology, length and corrosion depth of the corrosion pits on the surface of the corroded steel bars and the stress level is observed to reveal the stress corrosion cracking mechanism; the steel bar corrosion rate is calculated using the weight loss method, and the calculation formula for the steel bar corrosion rate under stress corrosion is obtained by statistical regression test data.
[0069] Embodiment 2:
[0070] A corrosion test method for implementing multiple stress levels of steel bars adopts natural corrosion. The specific steps are the same as those in Example 1, except that the measure of electrifying the test steel bars 11 to accelerate corrosion in step eight is eliminated.
[0071] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A corrosion test device for realizing multiple stress levels of steel bars, comprising a loading system, a chloride corrosion system and a test control system, characterized in that: The loading system includes a loading frame and a load driving device arranged on one side of the loading frame, the loading frame includes a left end plate and a right end plate arranged opposite to each other, a left cross plate and a right cross plate are movably arranged between the left end plate and the right end plate, and three independent steel bar test sections are formed inside the loading frame through the left cross plate and the right cross plate; the load driving device includes a through-core jack arranged on one side of the right end plate, the output end of the through-core jack is connected to the force transmission rod fixed on the right end plate, the input end of the through-core jack is connected to the output shaft end of the hydraulic pump connected to the oil pressure gauge, the force transmission rod passes through the right end plate and extends to the left end plate and is threadedly connected to one end of the connecting sleeve, the other end of the connecting sleeve is threadedly connected to the test steel bar, and the test steel bars of the three independent steel bar test sections are connected in series through the connecting sleeve and the force transmission rod.
2. A corrosion test device for realizing multiple stress levels of steel bars according to claim 1, characterized in that: The left end plate, right end plate, left transverse partition and right transverse partition are connected and fixed by two groups of upper and lower threaded rods which are symmetrically arranged up and down. A pair of steel pads are respectively arranged at the connection between the left end plate, right end plate, left transverse partition and right transverse partition and the upper and lower threaded rods, and are tightened and fixed by anchor nuts. The left end plate, right end plate, left transverse partition and right transverse partition are all made of solid steel plates with a thickness of 20 to 40 mm.
3. The corrosion test device for realizing multiple stress levels of steel bars according to claim 1, characterized in that: The chloride salt corrosion system comprises a corrosion tank, through holes are relatively provided on the tank body of the corrosion tank, the test steel bar is placed in the corrosion tank and passes through the through holes on both sides, the corrosion solution is poured into the corrosion tank, a stainless steel plate is provided on the lower side of the corrosion tank, the stainless steel plate and the test steel bar are respectively electrically connected to the negative electrode and the positive electrode of an external DC voltage-stabilized power supply through wires; an upper cover is connected to the top of the corrosion tank, a reference electrode and an auxiliary electrode are inserted into the corrosion tank through the reserved through slots of the upper cover, and the reference electrode, the auxiliary electrode and the test steel bar are respectively electrically connected to the electrochemical workstation of an external test and control system through wires.
4. A corrosion test device for realizing multiple stress levels of steel bars according to claim 3, characterized in that: The test control system also includes a strain gauge adhered to the surface of the test steel bar, and the strain gauge is electrically connected to the strain meter through a wire.
5. The corrosion test device for realizing multiple stress levels of steel bars according to claim 3, characterized in that: A rubber plug with a central penetration is provided at the junction of the through hole and the test steel bar, and an epoxy resin sealing layer is coated on the surface of the rubber plug.
6. The corrosion test device for realizing multiple stress levels of steel bars according to claim 3, characterized in that: The corrosion tank is made of acrylic material, and a drain valve is provided at the bottom of the corrosion tank.
7. The corrosion test device for realizing multiple stress levels of steel bars according to claim 1, characterized in that: The upper and lower threaded rods and the force transmission rods are all made of prestressed threaded steel bars, with diameters of 30 to 60 mm and standard tensile strength values of 785 to 1080 MPa.
8. A corrosion test method for implementing multiple stress levels of steel bars according to any one of 1 to 7, characterized in that: The corrosion is accelerated by electricity, including the following steps: Step 1: Adjust the positions of the left and right transverse partitions so that the test sections divided by them meet the test space required by each section of the test steel bars; Step 2: The test steel bar passes through the through hole reserved on the corrosion groove, and a rubber plug is sleeved on the surface of the test steel bar at the junction, and fits the outer pores of the corrosion groove; Step 3: Build the loading frame, and connect the dowel rod, connecting sleeve and test steel bar from left to right. The two ends of the connecting sleeve are respectively connected with the dowel rod and the test steel bar by threads. A pair of steel pads are respectively set at the connection between the left end plate, the left diaphragm, the right diaphragm, the right end plate and the dowel rod, and tightened and fixed by anchor nuts. Repeat this operation until the connection of the three independent steel bar test sections is completed, and the dowel rods of each section are fixed on the loading frame; Step 4: Grind the surface of the test steel bar exposed outside the corrosion tank until the surface is smooth and flat, paste the strain gauge on the polished part, and electrically connect the strain gauge to the strain meter through a wire; Step 5: Install a through-hole jack on one side of the right end plate of the loading frame and connect it to the force transfer rod. Slowly increase the load through a manual hydraulic pump, check the deviation of the load position, ensure that all components of the loading frame are operating normally, and then continue to apply the load steadily. When the oil pressure gauge reading reaches the set load, tighten the anchor nut to fix the force transfer rod on the right end plate. The load is transferred to each section of the test steel bar through the force transfer rod to maintain different stress states. Remove the through-hole jack to complete the load application, and then use epoxy resin to apply the rubber plug to seal the corrosion groove; according to the stress formula σ=F / A, the corrosion test of steel bars under different stress levels can be achieved, where σ is stress in MPa, F is the applied load in N, and A is the cross-sectional area of the test steel bar in mm 2 ; When the diameters of the test steel bars of each section are different and the cross-sectional areas A are different, corrosion tests of steel bars under various stress levels can be carried out simultaneously; Step 6: Prepare a saturated Ca(OH)2 solution as a corrosion solution, pour it into the corrosion tank, and keep the liquid level above the top surface of the test steel bar. Use the saturated Ca(OH)2 solution to simulate the concrete hole solution to soak the test steel bar for 8 to 10 days, so that a stable passivation film is formed on the surface of the test steel bar; after the steel bar is passivated, add analytical pure sodium chloride to the simulated concrete hole solution step by step to gradually increase its concentration range until the steel bar is depassivated; during this period, the concentration range increases by one level every 24 hours, and after each level of concentration increase, the open circuit potential of the test steel bar is tested using an electrochemical workstation, and whether the steel bar is depassivated is determined according to national standards; when the steel bar is depassivated, the accumulated chloride ion concentration in the simulated concrete hole solution is the critical chloride ion concentration; Step 7: The judgment condition of steel bar depassivation is: when the open circuit potential is greater than -250mV, it means that the steel bar is not depassivated; when the open circuit potential is between -250 and -400mV, it means that the steel bar may be depassivated; when the open circuit potential is less than -400mV, it means that the steel bar has been depassivated; Step 8: After the steel bar is depassivated, it enters the stress corrosion stage; a stainless steel plate connected to a wire is placed at the bottom of the container and connected to the negative electrode of the DC stabilized power supply. A wire is connected to the surface of the test steel bar and connected to the positive electrode of the DC stabilized power supply. The corrosion solution is used as the conductive medium to form a closed loop; the DC stabilized power supply is connected to the target current or voltage to start the accelerated corrosion process of the steel bar under continuous load; Step 9: Conduct electrochemical tests regularly. Before the test, turn off the DC regulated power supply to ensure that the corrosion solution is stable. The reference electrode is a saturated calomel electrode, the working electrode is the test steel bar, and the auxiliary electrode is a platinum electrode. They are electrically connected to the A, B, and C ports of the electrochemical workstation through wires to form a three-electrode test system. Set the relevant parameters of the electrochemical test, turn on the electrochemical workstation, and measure the polarization curve of the corroded steel bar; the linear polarization test overpotential ΔE is 70mV, polarization starts from the open circuit potential of -70mV and ends at the open circuit potential of +70mV. The polarization rate is 0.166mV / s, and the E-lgI curve is obtained. The instantaneous polarization current value I at the end of polarization is recorded, and the polarization curve is analyzed using the software lviumsoft that comes with the electrochemical workstation to obtain the corrosion current density i corr , or determined by the empirical formula: i corr =0.67i, i=I / A, where A is the polarization area of the steel bar, and I is the instantaneous current value when the steel bar ends polarization; after the test, for the accelerated corrosion condition of power-on, connect the DC regulated power supply to the target current or voltage, and continue the accelerated corrosion test; Step 10: Compare the corrosion current density obtained in step 9 with the international standard value to determine the corrosion degree of the steel bar. The international standard value of the corrosion current density is: corr The value is less than 0.1μA / cm 2 When the steel bar is not corroded, corr The value is 0.1~1μA / cm 2 When i corr Value is 1~10μA / cm 2 When i corr Value is 10~100μA / cm 2 When , it means that the steel bar corrosion rate is very high and a high degree of corrosion has occurred; Step 11: During the stress corrosion period, regularly observe the formation and expansion of corrosion holes and pits on the surface of the test steel bars, as well as the initiation and expansion of stress corrosion cracks, and take photos for archiving; Step 12: During the steel bar corrosion process, the real-time stress is calculated using Hooke's law based on the real-time strain measured by the strain gauge to monitor the stress loss of the steel bars in the corrosion test; when the strain decreases and the stress decreases, the anchor nuts at both ends of the loading frame are adjusted using a torque wrench to correct the stress to the target level; Step 13: The corrosion period t can be preliminarily calculated according to Faraday's law. Where, t is the power-on time; Z Fe is the valence of iron, which is 2; F is the Faraday constant, which is 96500C / mol; M loss is the preset steel bar mass loss, in g; M Fe is the molar mass of iron, take 56 g / mol; I corr is the corrosion current, in mA; Step 14: After reaching the preset corrosion level, the stress corrosion test is terminated; the corroded steel bars in the corrosion area are intercepted, and the relationship between the number and length of cracks on the surface of the corroded steel bars and the corrosion depth and stress level is observed to reveal the stress corrosion cracking mechanism; the steel bar corrosion rate is calculated using the weight loss method, and the calculation formula for the steel bar corrosion rate under stress corrosion is obtained by statistical regression test data.
Citation Information
Patent Citations
Device and method for metallic rod body material stress corrosion test
CN101109691A